BREACH OF CONTRACT AGAINST CONSUMERS IN CREDIT-BASED HOME PURCHASES AT DR HOUSING COMPLEX, BUKITTINGGI CITY - Satria Wahyudi (RADJA PUBLIKA, 2026)
This study discusses breach of contract against consumers in purchasing houses on credit at Housing Complex in Bukittinggi City. The purpose of this study is to identify the consequences of breach of contract experienced by consumers and the legal protection provided to the aggrieved consumers. This research uses an empirical juridical method with a qualitative approach, involving primary data from observations and interviews, as well as secondary data from legal literature and legislation. The results show that breaches such as delays in house handover and discrepancies in specifications cause both material and immaterial losses for consumers. Informal additional agreements that are not made formally and do not involve official developer parties weaken the consumers’ legal position. Legal protection regulated under the Civil Code and Law Number 8 Year 1999 on Consumer Protection has not been optimally implemented due to consumers’ lack of understanding, informal agreements, and complicated bureaucracy. The study recommends the necessity of formal agreements, increased supervision, legal education, and simplification of dispute resolution processes to strengthen legal protection for consumers of houses purchased on credit.